PF-1 Endometritis in Mix Breed Dog - IWY Semarariana; AAND Wisesa; PTE Sucitrayani; MPA Yunikawati; AANO Pujawan; PS Dwipartha; NMAS Paramita (Hemera Zoa, 2018)
Endometritis is an inflamation that happen in the endometrial tissue in the uterus that caused by pathogen bacterial infection [1]. Inflamation in the uterus also can caused by hormonal problem, post partus secondary infection, and distocia [2]. Endometritis without any proper medication can developt into pyometra.